Pentingnya Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan bagi Anak Sekolah Dasar - Alfyanti Alfyanti; Fitri Handayani Siregar; Ika Novita Padang; Jenni Romayanti Ginting; Sri Ayuning Melati; Fajar Sidik Siregar (Journal of Education Transportation and Business, 2024)
Physical Education is basically an integral part of the overall education system, Physical Education is an educational process that utilizes physical activity and is planned systematically aimed at improving individuals organically, neuromuscularly, perceptually, cognitively, socially and emotionally which focuses on developing aspects of physical fitness, skills movement, critical thinking skills, emotional stability, social skills, reasoning and moral action through physical activity. In the intensification of education as a process of human development that lasts a lifetime, the role of Physical Education is very important, namely providing opportunities for students to be directly involved in various learning experiences through systematic physical activities. The provision of learning experiences is directed at fostering, as well as forming a healthy and active lifestyle throughout life. There is no education that does not have pedagogical objectives, and there is no complete education without physical education, because motion as a physical activity is the basis for humans to know the world and themselves which naturally develops in line with the times and habituation of healthy lifestyles that lead to to stimulate balanced growth and development. The purpose of this study is to know and deepen knowledge about the importance of physical education, sports and health for elementary school-age children.